Subjective quality of life of those 65 years and older experiencing dementia. - Stewart-Archer, L.; Afghani, A.; Toye, Christine; Gomez, F. (2015)
BACKGROUND/OBJECTIVES: To describe how people experiencing dementia define quality of life and how this may be supported. DESIGN: Qualitative descriptive component of mixed methods cross-sectional study. SETTING: Western Canadian community (4-h weekly care minimum), supportive housing (24-h support/supervision), personal care homes (24-h nursing). PARTICIPANTS: One hundred and thirty-six persons aged 65+ experiencing dementia. MEASUREMENTS: Semi-structured interview questions. Rating of meeting life's goals. RESULTS: Participants characterised quality of life as: freedom, independence, having basic needs met, physical health, engagement in meaningful activities and tranquility. A need for self-determination/choice was evidenced across all domains. Increased access to skilled nursing care, support for meaningful engagement with family and meeting life's goals were endorsed as adding most to quality of life; 43% reported meeting all life's major goals. CONCLUSION: People experiencing dementia may have better quality of life when choice/self-determination is supported. Enhancements in care environment, independence, engagement and meeting of life's goals merit urgent attention.